EDUKASI KESEHATAN GINJAL DAN PEMERIKSAAN KREATININ URIN PADA IBU-IBU DI KELURAHAN GLUGUR DARAT 2 MEDAN - Nita Andriani Lubis; Gabriella Septiani Nasution; Sri Widia Ningsih (Poltekkes Kemenkes Bandung, 2022)
This activity is an implementation of the research we did before. WHO records the prevalence of chronic kidney failure worldwide at 8-16%. Kidney damage will cause an increase in urine creatinine. Community service for the Medical Laboratory Technology Study Program at the Health Polytechnic of the Ministry of Health Medan is carried out to provide health services that are implemented in the form of community service. The method of implementing the service provided is in the form of health education to increase mothers' knowledge about kidney health and urine creatinine examination. The target audience for this community service is women in Environment III, Glugur Darat 2 Village, East Medan District, totaling 40 people. The level of knowledge, attitudes and actions of respondents before (pre) intervention and after (post) intervention in kidney health education has increased. The 24-hour urine creatinine value measured in 40 respondents, the results were 1 person (3%) in the <normal group with thin BMI status, the normal group with 27 people (68%) with normal BMI status, and > normal group with 12 people (30 %) with details of 7 people with overweight BMI status and 5 people with obese BMI status. The results of statistical tests performed using the t-test BMI and 24-hour urine creatinine values ​​obtained significant values ​​(p<0.05). This shows that there is an increase in the knowledge, attitudes and actions of respondents before and after kidney health education, with BMI values ​​and 24-hour urine creatinine levels being directly proportional.